Integrated IT Governance Framework for a Sustainable Information Technology Roadmap at Universitas Negeri Manado - Batmetan, Johan Reimon (International Journal of Information Technology and Education, 2025)
Information technology (IT) governance has become a critical factor for higher education institutions in ensuring that digital investments align with strategic objectives while delivering long-term value. This study develops an integrated IT governance framework to design a sustainable information technology (IT) roadmap for Manado State University (UNIMA). Using a qualitative descriptive approach, the research employed the TOGAF Architecture Development Method (ADM) and COBIT 2019 to analyze the current state of ICT, identify governance gaps, and formulate a roadmap. Data were collected through interviews, surveys, observations, and document analysis involving university leaders, faculty representatives, and IT staff. The findings indicate that UNIMA’s ICT infrastructure is fragmented, with limited integration across academic and administrative systems, an absence of a formal IT governance committee, and a lack of alignment between IT initiatives and institutional goals. The proposed roadmap is structured into three horizons: short-term (1–5 years), focusing on establishing governance structures and integrating basic systems; medium-term (6–15 years), emphasizing development of integrated applications for research, community service, and student services; and long-term (16–25 years), achieving full digital transformation toward an ICT-based campus supported by big data, cloud computing, and artificial intelligence. This research contributes theoretically by contextualizing global IT governance models within Indonesian higher education and practically by providing a structured pathway for UNIMA’s digital transformation. The framework enhances institutional efficiency, strengthens academic and research competitiveness, and offers a scalable model for other universities pursuing sustainable ICT governance.